2018
DOI: 10.1038/s41598-018-35809-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Type 2 Diabetes mellitus induce lipopolysaccharide tolerance in rat neutrophils

Abstract: Obesity and diabetes implicate in various health complications and increased mortality caused by infection. Innate immune system is broadly affected by these diseases, leading the patients to an immunosuppressive state. A mechanism that leads innate immune cells to a less capacity of killing microorganism is the impaired TLR4 activation. TLR4 recognizes a component of the outer membrane of Gram-negative bacteria, lipopolysaccharide (LPS), and when activated increases the production of inflammatory substances. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 85 publications
0
42
0
Order By: Relevance
“…Type 2 diabetes is associated with worse outcomes and mortality caused by infection [31] due to impaired innate immune functions, including phagocytosis, cytokine and reactive oxygen species (ROS) production, bactericidal activity, and chemotaxis [32]. In our study, the GO analysis showed that the diabetic neutrophil response to molecules of bacterial origin, such as LPS, and inflammatory response were decreased.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Type 2 diabetes is associated with worse outcomes and mortality caused by infection [31] due to impaired innate immune functions, including phagocytosis, cytokine and reactive oxygen species (ROS) production, bactericidal activity, and chemotaxis [32]. In our study, the GO analysis showed that the diabetic neutrophil response to molecules of bacterial origin, such as LPS, and inflammatory response were decreased.…”
Section: Discussionmentioning
confidence: 61%
“…These data demonstrate that neutrophils from patients with diabetes may also exhibit impaired migration because of the downregulated chemotaxis, which may explain why some patients with diabetes have increased infection rates. Kuwabara et al showed that neutrophils had an impaired response to LPS in a type 2 diabetes and obesity animal model, and neutrophils from the GK rats were not capable of migrating to the site of inflammation due to the impaired expression of adhesion proteins after LPS stimulation [32]. In addition, a defect in the chemotaxis of leukocytes in patients with diabetes has been identified, which could contribute to increased infections in these patients [33,34], and high blood glucose induces a defective leukocyte-endothelial interaction in rats [35].…”
Section: Discussionmentioning
confidence: 99%
“…In T2D and obesity, neutrophils react with less production of reactive oxygen species upon PMA stimulation compared to metabolically healthy obese individuals [66]. Furthermore, a tolerance to LPS has been described in animal models of diabetes and obesity [67]. This innate immune dysfunction contributes to the high risk of infections in T2D and obesity [68].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GK rats exhibited a decrease in IL1-β, IL-6, and TNF-α concentration in BAL and also a reduction in the expression of adhesion molecules, such as LFA-1 and ICAM-2, on neutrophils. All these alterations were associated with a reduction in the TLR4 expression and activation in neutrophils [54].…”
Section: Impaired Neutrophil Migration In Diabetesmentioning
confidence: 94%